Dr. José Gregorio Hernández: the first microbiologist saint (Mayéutica Revista Científica de Humanidades y Artes, 2025)
This article briefly describes an important event for the Catholic Christian community in Venezuela: the canonization of its first saint and, even more surprisingly, the first microbiologist saint in world history. After 106 years, following his death for sanctification, popular fervor remains alive around the Venezuelan saint whom the Vatican recognized for healing many sick people around the world, with hundreds of families documenting their gratitude for the favors received.
Keywords: José Gregorio Hernández; Microbiology; Medicine; Catholic sainthood; Venezuela